Easements relating to land surveying and title examination - Wilson, Donald A., 1941-; Wiley eBooks (Hoboken, N.J. : John Wiley & Sons, 2013)
Concise, in-depth coverage of the complex issues of easements and their reversion The definition, use, defense, and retirement of easements are areas of active work for land surveyors, lawyers, and the holders and buyers of easements, such as utility companies and highway departments. Easements Relating to Land Surveying and Title Examination is the most up-to-date reference that succinctly and incisively covers easements and reversions, written for land surveyors and title examiners. This comprehensive guide covers the various forms of easements, their creation, rever.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Servitudes -- United States; Surveying -- Law and legislation -- United States; Land titles -- United States; LAW -- Administrative Law & Regulatory Practice; Land titles; Servitudes; Surveying -- Law and legislation; United States; Electronic books